The Kajian Manfaat Tumbuhan Kepuh (Sterculia Foetida L.) Dan Terapi Yoga Sebagai Pengobatan Tradisional - Ni Wayan Rika Kumara Dewi; Iwan Saka Nugraha; Made Prita Artika (UHN IGB Sugriwa Denpasar, 2023)
Kepuh plant (Sterculia foetida L.) is one of the plants that have the potential as a source of new medicines which are rich in compounds used as modern medicines, pharmaceutical intermediates, and main compounds in natural medicinal ingredients. Traditional medicine in Bali is often called Usada which contains the science of diagnosing diseases, medicinal ingredients, and prayers. The community is also familiar with Ayurveda, namely the use of herbal medicines and yoga therapy. The development of traditional medicine into herbal medicine requires an analysis of the activity of primary metabolites present in the Kepuh plant (Sterculia foetida L.). In addition, it is also necessary to know the effect of yoga therapy on traditional medicine. This study uses a descriptive method using a structured article review method. Based on secondary data obtained from several scientific journals, it is known that the biological activities of secondary metabolites in the Kepuh plant (Sterculia foetida L.) are antibacterial, antioxidant, antifungal, antiprotozoal, cytotoxic, thrombolytic, anti-rheumatic, analgesic, antipyretic, antidiabetic, insecticidal, antifeedant, and microbicidal effects. So scientifically the Kepuh plant (Sterculia foetida L.) can be used as a source of new drugs which are rich in compounds used as modern medicines, pharmaceutical intermediates, and main compounds in natural medicinal ingredients. Likewise, the effect of giving yoga therapy to traditional medicine which is a non-pharmacological treatment can help the healing process in patients with certain diseases. However, it is necessary to carry out further research on the use of the Kepuh plant as a herbal medicine in combination with yoga therapy.